2021
DOI: 10.3389/fvets.2021.616865
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Tsetse Flies and Ticks Using Insecticide Treatment of Cattle in Tororo District Uganda: Cost Benefit Analysis

Abstract: Background: The endemic vector-borne diseases transmitted by tsetse and ticks impose heavy burdens on the livestock keepers in Africa. Applying deltamethrin to the belly, legs, and ears of cattle offers a possibility of mitigating these losses at a cost affordable to livestock keepers. Although studies have quantified the impacts of individual diseases on livestock productivity, little is known about the dual economic benefits of controlling both tsetse and ticks, nor about the number of cattle that need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Tsetse control activities are also carried out in a number of countries in which rhodesiense HAT is endemic, including Kenya [ 38 ], Malawi [ 39 ], United Republic of Tanzania [ 40 , 41 ], Uganda [ 42 ], Zambia [ 43 ] and Zimbabwe [ 44 ], where interventions against the tsetse vector are primarily driven by the need to control animal trypanosomiasis; interventions are normally implemented by veterinary services and livestock keepers. However, the benefits to One Health of tsetse control are well recognized both nationally and internationally [ 45 ], and they are explicitly pursued in many areas [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tsetse control activities are also carried out in a number of countries in which rhodesiense HAT is endemic, including Kenya [ 38 ], Malawi [ 39 ], United Republic of Tanzania [ 40 , 41 ], Uganda [ 42 ], Zambia [ 43 ] and Zimbabwe [ 44 ], where interventions against the tsetse vector are primarily driven by the need to control animal trypanosomiasis; interventions are normally implemented by veterinary services and livestock keepers. However, the benefits to One Health of tsetse control are well recognized both nationally and internationally [ 45 ], and they are explicitly pursued in many areas [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, those who used both vector control and drug treatment had fewer cases of AAT than those who only used drug treatment. It has been suggested that treating cattle population with insecticide leads to increased benefit costs, increased killing of tsetse flies, and reduction of Trypanosoma species in cattle and cattle trypanosomiasis [ 73 , 74 ]. Similar results have been reported in Uganda and Tanzania [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that treating cattle population with insecticide leads to increased benefit costs, increased killing of tsetse flies, and reduction of Trypanosoma species in cattle and cattle trypanosomiasis [ 73 , 74 ]. Similar results have been reported in Uganda and Tanzania [ 73 , 74 ]. Thus, the integrated use of trypanocidals and insecticides can effectively reduce cattle AAT levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in this study, we show that for "slow" pathogens like rHAT, effective treatment strategies can sufficiently reduce the spread of rHAT. It has been shown that treatment of cattle using diminazene aceturate and spraying for tsetse flies to protect cattle against trypanosomiasis is effective and has high net benefits (86)(87)(88). Compared to "slow" pathogens such as rHAT, control of "fast" pathogens within the network may be problematic and costly requiring a wider coverage of cattle markets or a highly effective control method or methods.…”
Section: Discussionmentioning
confidence: 99%